Effect Of Strain And Age On Bone Integrity Of Commercial Broiler Chickens (2016)
Skeletal disorders and leg problems cause varying degree of economic losses in broiler birds. This study was aimed at investigating the effect of strain and age on bone integrity of some broiler strains available to poultry farmers in Nigeria using morphometric and mechanical indices. Four hundred (400) one day old chicks comprising of 100 each of Arbor Acre (AA), Hubbard (HB), Marshal R (MR) and Marshal Y (MY) strains were raised for a period of 42 days. The birds were fed similar diet at the starter and finisher phases. At the end of each week, 4 birds were randomly selected from each of the group and sacrificed, femur and tibiotarsal (left and right) bones were obtained from each of the bird for analyses. Body Weight (BW), Femur Weight (FW), Femur Length (FL), Tibia Weight (TW), Tibia Length (TL), Weight/Length Index (WLI), Diaphysis Diameter (DD), Relative Bone Density (RBD), Robusticity Index (RBT) and Tibiotarsal Index (TI) were recorded each week. Mechanical parameters were evaluated using the universal testing machine: Force, Moment of Inertia (MI), Stress and Modulus of Elasticity (ME). Mean values of Mechanical indices of the femur bone was significant at Day 42 with AA Strain having the least mean value of force and MY Strain with highest value of ME. The results of tibiotarsal bone revealed that MY Strain had highest mean value of force, ME and Stress across the weeks. Conclusively, Marshal Y strain was found to have better bone integrity than the other groups